Floristic catalogue of the Duraton Canyon (Segovia), V. Alismataceae to Orchidaceae - Cebolla, Consuelo; Rivas, María Antonia; Soriano, Carlos (Lazaroa, 2014)
This report completes the series devoted to the Floral catalogue of the Duraton river Canyon, which has been published in Lazaroa. 111 taxones of Monocotiledoneae (Liliatae) are refeted.